THE INFLUENCE OF OFFICIAL TIKTOK HANASUI VIDEO CONTENT ON BRAND AWARENESS AND CONSUMER BUYING INTEREST IN SOLO RAYA - Kurniansyah, Alfrico Windu; Wulandari, Anggi; Harminingsih, Diva Yuni; Rachman, Faizal Nur; Kusuma, Pradipta Eva (Jurnal Manajemen Bisnis dan Terapan, 2000)
TikTok is considered as one of the means to promote products. This phenomenon provides an opportunity for beauty companies to utilize TikTok as a tool to increase brand awareness and consumer buying interest. This study aims to examine the significance of the influence of Hanasui's official Tiktok content on brand awareness and purchase intention of Hanasui products. This research adopts a descriptive quantitative approach using descriptive quantitative research methods. The minimum sample size taken was 42 respondents by applying non-probability sampling through purposive sampling technique. Data collection was carried out through questionnaire distribution, and data analysis was carried out using simple linear regression analysis. The results showed a positive and significant effect of TikTok Hanasui Official video content on the variables of brand awareness and purchase intention of Hanasui products. These findings indicate that utilizing the TikTok platform in marketing strategies can help companies increase brand awareness and product purchase intention. Beauty companies can consider using Tik Tok as one of the tools to increase the marketing effectiveness of their products. Hanasui Official's Tiktok video content has a positive influence on brand awareness and purchase intention, companies can design more focused and efficient marketing strategies.